Conversion of asymptomatic infection to symptomatic visceral leishmaniasis: A study of possible immunological markers - Das, Vidya Nand Rabi; Bimal, Sanjiva; Siddiqui, Niyamat Ali; Kumar, Ashish; Pandey, Krishna; Sinha, Sanjay Kumar; Topno, Roshan Kamal; Mahentesh, Vijay; Singh, Ashish Kumar; Lal, Chandra Shekhar; Singh, Subhankar Kumar; Das, Pradeep (PLOS Neglected Tropical Diseases, 2020)
Introduction Presence of asymptomatic individuals in endemic areas is common. The possible biomarkers in asymptomatic individuals once they get exposed to infection as well as following conversion to symptomatic disease are yet to be identified.We identified asymptomatic Visceral leishmaniasis (VL) infection amongst rK39+sorted direct agglutination test positive (DAT+) endemic healthy population and confirmed it by quantitative PCR(qPCR).The immunological determinants such as Adenosine deaminase (ADA), Interferon gamma (IFN-γ), Tumour Necrosis Factor alpha (TNF-α) and Interleukin 10 (IL-10)were examined to predict probable biomarkers for conversion to symptomatic VL. Methods Sample size was 5794 healthy individuals from VL endemic region. Antibody tests(DAT &rK39) were performed and later a qPCR assay was employed using kDNA specific primers and probes. Immunological biomarkers examined were ADA level by ADA–MTP kit and quantitative cytokines(IFN-γ, IL-10 and TNF-α) by ELISA. Results 120 asymptomatic individuals of 308 rK39 sero-positives were DAT positive comprising of 56 with previous history and 64 with no history of VL. RT-PCR confirmed asymptomatic VL in 42 sero-positives. These were followed up through repeated qPCR and evaluation of immunological determinants. We observed10 symptomatic cases converted from a total of 42 asymptomatic individuals identified at base-line. The level of ADA, IL-10 and IFN-γ remained consistently high in asymptomatic cases and amongst these, ADA and IL-10 but not IFN-γ remained higher at the development of clinical symptoms into active VL. On the contrary, there was no significant change in the mean concentration of TNF-α at both stages of the disease. Discussion We surmise from our data that considerable proportion of asymptomatic cases can be a reservoir and may play a crucial role in transmission of visceral leishmaniasis in endemic areas. The data also suggests that ADA and IL-10 can serve as a potential biomarker during the conversion of asymptomatic into symptomatic VL.